PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) - Fitri, Reni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The research aimed to show the increasing the students comprehensive reading ability by using DRTA strategy. This research was action research, and it was carried on two cycles. This research used quantitative and qualitative approach. Subject of this research were teacher and the second grade studen of elementary school. It was found that DRTA strategy improve the students comprehensive reading ability. Kata kunci : membaca pemahaman; strategi DRTA